TINGKAT PENDIDIKAN DAN DUKUNGAN SUAMI BERKAITAN DENGAN KECEMASAN MENGHADAPI MENOPAUSE PADA WANITA PREMENOPAUSE - Apriana Ama; Ronasari Mahaji Putri; Hilda Mazarina Devi (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2022)
The phenomenon of many premenopausal women express anxiety about menopause. The level of education and husband's support is less suspected to increase anxiety in premenopausal women. Relating the relationship between education level, husband's support with anxiety facing menopause in premenopausal women is the aim of the study. The study design was cross sectional, with a population of 55 'premenopausal' women aged 40 - 45 years, 48 ??sample respondents were found. with determination using simple random sampling. The instrument uses a questionnaire. Data analysis using Fisher's Exact test. The results of the study mostly (52.1%) of respondents' husbands had junior high school education; most (60.4%) respondents have less husband support; most (56.2%) of respondents experienced menopause anxiety; and there is a relationship between the level of education and husband's support with anxiety facing menopause in premenopausal women in Petungsewu Village, Dau Malang District, obtained p value = (0.000) < (0.05). Further researchers are expected to involve husbands as respondents so that they know directly the husband's support for his wife.